2020
DOI: 10.1021/acsbiomaterials.9b01939
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Type I and II Blend Hydrogel with Autologous Mesenchymal Stem Cells as a Scaffold for Articular Cartilage Defect Repair

Abstract: Collagen type II is a promising material to repair cartilage defects since it is a major component of articular cartilage and plays a key role in chondrocyte function. This study investigated the chondrogenic differentiation of bone marrowderived mesenchymal stem cells (MSCs) embedded within a 3:1 collagen type I to II blend (Col I/II) hydrogel or an all collagen type I (Col I) hydrogel. Glycosaminoglycan (GAG) production in Col I/II hydrogels was statistically higher than that in Col I hydrogels or pellet cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 81 publications
1
59
0
Order By: Relevance
“…Previous studies have shown that type I collagen promotes the proliferation of chondrocytes and that type II collagen supports the chondrogenic differentiation of MSCs [ 59 , 60 ]. The results from this study suggest that there is clinical value in the cartilage repair capabilities of Col I/II hydrogel with encapsulated MSCs [ 61 , 62 ]. Nonetheless, the long-term performance of pure type I collagen may be compromised by significant shrinkage and weak mechanical properties [ 63 , 64 ].…”
Section: Applications Of Biomaterials In 3d Cell Culturementioning
confidence: 99%
“…Previous studies have shown that type I collagen promotes the proliferation of chondrocytes and that type II collagen supports the chondrogenic differentiation of MSCs [ 59 , 60 ]. The results from this study suggest that there is clinical value in the cartilage repair capabilities of Col I/II hydrogel with encapsulated MSCs [ 61 , 62 ]. Nonetheless, the long-term performance of pure type I collagen may be compromised by significant shrinkage and weak mechanical properties [ 63 , 64 ].…”
Section: Applications Of Biomaterials In 3d Cell Culturementioning
confidence: 99%
“…For example, articular cartilage and vitreous fluid contain predominantly collagen type II, but it is challenging to make structurally robust collagen type II hydrogels. Our lab therefore designed hydrogels by copolymerizing collagen type I and type II to harness the biological activity of collagen type II and the improved mechanical properties of collagen type I for articular tissue engineering [ 44 , 45 ]. Bioprinted collagen type II hydrogels with chondrocytes have also been designed to form biomimetic hydrogels with cell density gradients to mimic cartilage zones [ 46 ].…”
Section: Collagen Alone With No Crosslinkersmentioning
confidence: 99%
“…Mainly because there are no vascular channels, the conversion of stable chondrocytes into deficient locations and low protein efficiency typical of the adjacent extracellular matrices are inadequate. The combined administration to cartilage defect site of suitable cells, scaffolds and biological factors will contribute toward the structural and functional restoration of damaged tissues (Reimann et al., 2017 ; Kilmer et al., 2020 ; Mancipe Castro et al., 2020 ). Therefore, the challenge in orthopedics lies in an appropriate procedure for the reconstruction of joint cartilage defects.…”
Section: Introductionmentioning
confidence: 99%